AKIBAT HUKUM KETERLAMBATAN MENDAFTARKAN AKTA KELAHIRAN ANAK DITINJAU DARI UNDANG-UNDANG NOMOR 23 TAHUN 2003 TENTANG PERLINDUNGAN ANAK DAN PEREMPUAN (STUDI KASUS DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN FLORES TIMUR) - Hotan, Max Erwin Grandi; Aloysius, Sukardan; Mauritsius, Darius (Petitum Law Journal, 2023)
The state of Indonesia, which is a state of law, should have a society that is aware of the law. One form of awareness of the Indonesian people towards the law is to realize how important and necessary it is for someone to have written evidence in determining the status of that person for events or events that always exist. in the course of human life, among others; marriage events, birth events, child recognition or legalization events, divorce events and by registering the event or incident at the Civil Registry Institution in the form of a Civil Registry Deed. This is in accordance with the law in the Decree of the Minister of Home Affairs Number 54 of 1999 concerning Guidelines for the Implementation of Population Registration in articles 3 and 5 which essentially states that every resident and temporary resident is obliged to register and register every event of birth, marriage, divorce and death listed in the Deed of Population Registration. The formulation of the problem that will be examined by the author is (1) What are the legal consequences if someone is late in registering a birth certificate in terms of Law No. 23 of 2003. (2) What is the proper procedure in registering a birth certificate for those who are too late to register according to Law No. 23 of 2003. This study uses an empirical juridical method, namely research whose data is obtained directly from interviews with respondents in the research field to investigate the legal reality that exists in social life. Data processing techniques using editing, coding and tabulating techniques. The respondents were the Head of the East Flores Regency Dispenduk, Civil Registration Service Division, People who were Late in Registering a Birth Certificate. and data analysis techniques using descriptive qualitative analysis. The results of the study show: (1) Legal Consequences If Someone is Late in Registering a Birth Certificate In terms of Law No. 23 of 2003, the ADMINDUK Act if there is a delay in registering a child's birth certificate is usually subject to sanctions. (2) Appropriate Procedures in Registering Birth Certificates for those who are late in registering according to Law No. 23 of 2003. Applicants enter data, birth form data filled in from the village, original birth information from the hospital or from the village, and even then giving birth at home.